CT Measured Cardiovascular and Metabolic Risk Factors in Patients With COVID-19 Infections - Ulu, Esra Meltem Kayahan; Terzi, Ozlem (Galenos Publ House, 2022)
Objective: The aim of this study was to document some measurable thoracic computed tomography (CT) parameters investigated as a risk factors for prognosis in patients with coronavirus disease-2019 (COVID-19). Materials and Methods: We retrospectively analysed the patients with COVID-19 infection in three groups. Group 1 patients were the patients who were treated in the inpatient clinic or at home for COVID-19 pneumonia, group 2 patients consisted of patients who survived after treatment for COVID-19 pneumonia in intensive care unit (ICU), group 3 patients consisted of patients who died during treatment for COVID-19 pneumonia in the ICU. We evaluated the diameter of the aorta (A) and pulmonary artery (PA), PA/A ratio, cardiothoracic ratio (CTR), the fat to muscle ratio, and paraspinal muscle density as CT parameters evaluated as risk factors for COVID-19 infection. Results: The median age of all patients was 67 (Q1: 58-Q3: 75) and 60,6 % (n=143) of the patients were male. CTR was the only parameter for admission to ICU found statistically significant in multivariate analysis for both men and women. Additionally, it was the only significant risk factor for death in patients with COVID-19 infection. Although not statistically significant, the diameter of PA was found to be high in all groups. The other parameters evaluated did not provide statistically significant results between the groups. Conclusion: CTR may be taken into consideration as a potential risk factor in the evaluation of the patients with COVID-19 infections The diameter of PA was found to be higher in all groups so it might be an indicator of inflammation of the lungs.
Keywords: CT; COVID-19; Metabolic